ICT as strategy in the use and domain of irregular verbs in the affirmative and interrogative form. - Albán Tinoco, Carlos Alberto (Machala : Universidad Técnica de Machala, 2015)
Este proyecto de investigación científica tiene como objetivo principal establecer la mejor estrategia que los maestros pueden utilizar los verbos irregulares de enseñanza y las reglas gramaticales en el pasado simple lenguaje del Inglés a los estudiantes del segundo año de la escuela secundaria Machala.
This scientific research project has as main objective to establish the best strategy that the teachers can use teaching irregular verbs and grammar rules in the simple past tense the English language to the students of the second year of high school Machala.
Keywords: STRATEGY; IRREGULAR VERBS; AFFIRMATIVE FORM; INTERROGATIVE FORM